CETC2013 conference on electronics, telecommunications and computers - Fantoni, Alessandro (2013)
CETC 2013 is a premier conference in the broad field of Electronics, Telecommunications and Computers. The aim of the conference is to provide a platform for engineers to disseminate and discuss their current research findings and also to explore recent development, current practices and future trends in Electronics, Telecommunications and Computers. We also encourage the dissemination of R&D linked to the Industry. The conference program includes sessions with invited speakers and breakout sessions with oral and poster presentations in the fields of Electronics, Telecommunications, and Computers.